Consumo de carnes en zonas cálidas del Nuevo Reino de Granada : cualidades cambiantes, siglos XVI y XVII (2006)
ABSTRACT: The article deals on the production and consumption of pork and meats from some American animals in the high-traffic comercial temperate zones of the New Kingdom of Granada, during the 16 th and 17 th centuries. The objective is to show that the increase in the carbon consumption of meat, as compared to the Mediterranean European diet, production changes in the colonial society’s concepts on life. Additionally, it shows that amida an atmosphere of Hispanic domination, certain indigenous traditional uses of American animal meats were transformed drastically, beginning to be used for supplying cities, villas and ports. The investigation is based on information from the fondo Visitas del Archivo General de la Nación (Bogotá) and from printed sources, some of which have been of notably infrequent use in the studies on the New Kingdom of Granada.